The Importance of Social Support, Optimism and Resilience on the Quality of Life of Cancer Patients - Ruiz-Rodríguez, Iván; Hombrados-Mendieta, Isabel; Melguizo-Garín, Anabel; Martos-Méndez, María José (Frontiers in Psychology, 2022)
Introduction: The aim of the present study is to carry out a multidimensional analysis on the relation between satisfaction with social support received, resilience and optimism in cancer patients and their quality of life. Materials and Methods: Data were gathered through questionnaires fulfilled by 142 cancer patients. Data relate to socio-demographic, health, quality of life, social support, resilience, and optimism. Results: Satisfaction with the sources and types of support, resilience and optimism relates positively with quality of life. Predictive models show that informational support from friends is the variable that most increases patients’ general health, while emotional support from the partner is the one that best improves how patients cope with the disease. In the same line, emotional support from the partner, together with informational support from family are the ones that most contribute to reduce patients’ symptoms. Resilience improves general health and functioning, and reduces symptoms. Patients’ optimism and resilience also reduce symptoms. Gender differences were found, with females showing lower quality of life than males, mainly in how they cope with cancer. Patients 21 in the stage of treatment showed lower quality of life and higher symptoms. Such increase was 22 observed in patients who received hormonotherapy or chemotherapy. Discussion: Important practical implications can be drawn from results, which could help improve cancer patients’ quality of life through intervention strategies aimed at increasing their resilience, optimism, and the social support provided by their closer sources.